Hybrid coronary revascularization versus conventional coronary artery bypass grafting: Systematic review and meta-analysis. Issue 33 (August 2018) - Reynolds, Alexander C.; King, Nicola
Abstract: Background: Hybrid coronary revascularization (HCR) combining minimally invasive grafting of the left internal mammary artery to the left anterior descending artery with percutaneous coronary intervention has become a viable option for treating coronary artery disease. The aim of this meta-analysis was to compare HCR with conventional coronary artery bypass grafting (CABG) in a range of clinical outcomes and hospital costs. Methods: To identify potential studies, systematic searches were carried out in various databases. The key search terms included "hybrid revascularization" AND "coronary artery bypass grafting" OR "HCR" OR "CABG." This was followed by a meta-analysis investigating the need for blood transfusion, hospital costs, ventilation time, hospital stay, cerebrovascular accident, myocardial infarction, mortality, postoperative atrial fibrillation, renal failure, operation duration, and ICU stay. Results: The requirement for blood transfusion was significantly lower for HCR: odds ratio 0.38 (95% confidence intervals [CIs] 0.31–0.46, P  < .00001) as was the hospital stay: mean difference (MD) −1.48 days (95% CI, −2.61 to −0.36, P  = 0.01) and the ventilation time: MD −8.99 hours (95% CI, −15.85 to −2.13, P  = .01). On the contrary, hospital costs were more expensive for HCR: MD $3970 (95% CI, 2570–5370, P  < .00001). All other comparisons were insignificant. Conclusions: In the short-term, HCR is as safe as conventional CABG and may offer certain benefits such as a lower requirement for blood transfusion and shorter hospital stays. However, HCR is more expensive than conventional CABG. Abstract : Supplemental Digital Content is available in the text